Philodendron fibraecataphyllum (Araceae), a new species from the lowlands in Western Colombia and Ecuador - Mora, M. Marcela; Croat, Thomas B. (Phytotaxa, 2016)
We describe a new species of Philodendron subgenus Philodendron from the lowlands of the Pacific Coast of Colombia and Ecuador. The new species is compared with P. acuminatissimum and P. balaoanum, two similar species from western Ecuador.